The Relationship between Clean Water Facilities and Latrine Use with the Incidence of Diarrhea in Toddlers in KB Bagan Percut Village, Percut Village, Deli Serdang - Nanda, Meutia; Riskiya Sibarani, Adinda Azima; Rizki, Aprida Aulia; Rizqika, Indah; Hazrin, Yosita (Fakultas Ilmu Kesehatan, 2025)
Diarrhea is an environmental-based disease, the factors that cause this disease are influenced by clean environmental sanitation and the use of latrines, because if these two facilities are contaminated, there is a risk of being infected with diarrhea. The aim of this research is to determine the relationship between clean water facilities and the use of latrines with the incidence of diarrhea in toddlers in the KB village of Percut Village. This research was carried out in KB Bagan Percut Village, Percut Village, Percut Sei Tuan District. This type of research is quantitative with the nature of an analytical description with a cross-sectional method. The population in this study was all 256 mothers with toddlers registered at the health center and the total sample in the study was 72 toddlers. Based on the results of the analysis using statistical tests, the data showed that there was a correlation between clean water facilities (p = 0.003) < 0.05 and latrine use (p = 0.000) < 0.05 with the incidence of diarrhea in toddlers in KB Bagan Percut Village, Percut Village, District Percut Sei Tuan. Based on the results of the research, it was concluded that there was a significant relationship between clean water facilities and the use of toilets on the incidence of diarrhea in toddlers in the KB Bagan Percut village in Percut Village, Percut Sei Tuan District. It is recommended that Village Officials and Health workers carry out outreach, outreach and supervision in the procurement and use of clean water facilities and types of toilets that meet the requirements.